PENGARUH LITERASI KEUANGAN, PERSEPSI KEGUNAAN, KEAMANAN, DAN FITUR TERHADAP MINAT PENGGUNAAN BANK DIGITAL : (STUDI PADA GENERASI Z DI SURABAYA PENGGUNA SEABANK) - Kazza Savanah Zubaidi; Anik Yuliati (Politeknik Negeri Ambon, 2025)
Introduction: This study focuses on evaluating the extent to which financial literacy, perceived usefulness, security, and service features influence individuals' interest in using digital banking services. The growing utilization of digital financial applications among the younger generation highlights the need for a deeper understanding of the factors that shape their preferences, particularly regarding SeaBank, which is emerging as a promising digital payment platform. Method: A quantitative approach was employed, involving participants from Generation Z residing in Surabaya. A total of 100 respondents were selected using a random sampling technique, with the sample size determined through the Slovin formula at a 10% margin of error. Data were collected through an online questionnaire using 1 5-point Likert scale. The data were analyzed using the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS), processed with SmartPLS version 4.0 to assess the relationships among the variables in the research model. Results:The findings reveal that perceived usefulness and security have a positive and significant impact on the intention to use digital banking. Meanwhile, financial literacy and service features also show a positive influence, although their effects were found to be statistically insignificant. Keywords: financial literacy, perceived usefulness, security, features, intention to use